Posterior Surgery for Adolescent Idiopathic Scoliosis With Pedicle Screws and Ultrahigh–Molecular Weight Polyethylene Tape: Achieving the Ideal Thoracic Kyphosis. Issue 8 (October 2016) - Imagama, Shiro; Ito, Zenya; Wakao, Norimitsu; Ando, Kei; Hirano, Kenichi; Tauchi, Ryoji; Muramoto, Akio; Matsui, Hiroki; Matsumoto, Tomohiro; Sakai, Yoshihito; Katayama, Yoshito; Matsuyama, Yukihiro; et al.
Abstract : Study Design: Prospective clinical case series. Objectives: To describe our surgical procedure and results for posterior correction and fusion with a hybrid approach using pedicle screws, hooks, and ultrahigh–molecular weight polyethylene tape with direct vertebral rotation (DVR) (the PSTH-DVR procedure) for treatment of adolescent idiopathic scoliosis (AIS) with satisfactory correction in the coronal and sagittal planes. Summary of Background Data: Introduction of segmental pedicle screws in posterior surgery for AIS has facilitated good correction and fusion. However, procedures using only pedicle screws have risks during screw insertion, higher costs, and decreased postoperative thoracic kyphosis. We have obtained good outcomes compared with segmental pedicle screw fixation in surgery for AIS using a relatively simple operative procedure (PSTH-DVR) that uses fewer pedicle screws. Methods: The subjects were 30 consecutive patients with AIS who underwent the PSTH-DVR procedure and were followed for a minimum of 2 years. Preoperative flexibility, preoperative and postoperative Cobb angles, correction rates, loss of correction, thoracic kyphotic angles (T5–T12), coronal balance, sagittal balance, and shoulder balance were measured on plain radiographs. Rib hump, operation time, estimated blood loss, spinal cord monitoring findings, complications, and scoliosis research society (SRS)-22 scores were also examined. Results: The mean preoperative curve of 58.0 degrees (range, 40–96 degrees) was corrected to a mean of 9.9 degrees postoperatively, and the correction rate was 83.6%. Fusion was obtained in all patients without loss of correction. In 10 cases with preoperative kyphosis angles (T5–T12) <10 degrees, the preoperative mean of 5.8 degrees improved to 20.2 degrees at the final follow-up. Rib hump and coronal, sagittal and shoulder balances were also improved, and good SRS-22 scores were achieved at final follow-up. Conclusions: The correction of deformity with PSTH-DVR is equivalent to that of all-pedicle screw constructs. The procedure gives favorable correction, is advantageous for kyphosis compared with segmental screw fixation, and uses the minimum number of pedicle screws. Therefore, the PSTH-DVR procedure may be useful for treatment of idiopathic scoliosis.